Dynamics of Marginalized Rohingya Refugees’ Lives in Aceh from an Islamic Family Law Perspective - Asnita, Dessy; Matahari, Ladisa Oktari; Agustinar, Agustinar (USRATY : Journal of Islamic Family Law, 2025)
This study explores the dynamics of marginalized Rohingya refugees’ lives in Aceh from the perspective of Islamic family law. Using a qualitative approach with a case study design, the research integrates field observations, in-depth interviews, and normative legal analysis to understand the intersection between social marginalization and family law issues. The findings indicate that Rohingya refugees face multidimensional marginalization encompassing social exclusion, economic instability, and legal uncertainty in family matters such as marriage registration, guardianship, inheritance, and the protection of women and children. The Acehnese community’s attitudes toward the refugees have transformed from initial humanitarian sympathy to social resistance, shaped by misinformation, cultural differences, and limited coordination between governmental and humanitarian institutions. These challenges have exacerbated the vulnerability of refugee families, particularly in gaining access to legal identity and family protection under Indonesian law. From an Islamic family law perspective, the study emphasizes that the principles of ukhuwah Islamiyah, justice (al-‘adl), and public welfare (maslahah ‘ammah) should guide the protection of refugee families as part of the broader Islamic humanitarian responsibility. The study concludes that strengthening the synergy between Sharia principles and Indonesian positive law is essential to create an inclusive legal framework that ensures dignity, justice, and protection for marginalized communities. Academically, this research contributes to contemporary discussions on Islamic family law by offering a normative and socio-legal framework for addressing refugee family issues within Muslim-majority societies.